2006
DOI: 10.1007/s11238-006-0006-z
|View full text |Cite
|
Sign up to set email alerts
|

The Effectiveness of Assigned Goals in Complex Financial Decision Making and the Importance of Gender

Abstract: Evidence suggests that men are more confident and less risk averse in financial decision making. Researchers did not address how men and women respond differently to goals in financial decision situations, however. In the present study, men set more challenging personal goals and risked more resources than women in a complex financial decision task. Men did not report higher self-efficacy versus women. As expected, gender interacted with assigned goals to predict self-efficacy, risk behavior, and personal goal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 65 publications
0
6
0
Order By: Relevance
“…In support of this proposition, d'Acremont and Van der Linden [20] compared risk-related decision making in adolescents and found that girls, but not boys, learned to make better decisions during the Iowa Gambling Task, in which selecting from risky decks of cards leads to greater overall losses [21] . Furthermore, some evidence indicates that when externally-provided risk taking goals are more difficult, males risk more than females, whereas the opposite is true when assigned risk taking goals are easy [22] . There are also sex differences in how much an individual's risk tolerance influences group decisions.…”
Section: Introductionmentioning
confidence: 99%
“…In support of this proposition, d'Acremont and Van der Linden [20] compared risk-related decision making in adolescents and found that girls, but not boys, learned to make better decisions during the Iowa Gambling Task, in which selecting from risky decks of cards leads to greater overall losses [21] . Furthermore, some evidence indicates that when externally-provided risk taking goals are more difficult, males risk more than females, whereas the opposite is true when assigned risk taking goals are easy [22] . There are also sex differences in how much an individual's risk tolerance influences group decisions.…”
Section: Introductionmentioning
confidence: 99%
“…In general, males outperform females in spatial and quantitative tasks, while females exceed males in verbal ability (Hyde and Linn 1988;Linn and Petersen 1985;Masters and Sanders 1993;Voyer, Voyer, and Bryden 1995). Moreover, gender differences were detected in motivation (Klein and Hodges 2001;Rogers et al 1998), risk-taking behavior,r and decision making (Endres 2006;Larkin and Pines 2003;Ronay and Kim 2006). As such, it is conceivable that the effect of motivational orientation may differ according to the gender of the forecaster.…”
Section: Gender Differences and Task Performancementioning
confidence: 98%
“…26 Self-efficacy is a mediating mechanism of personal agency that mediates between the sources of its creation and subsequent outcomes. 27 The predictive and mediational role of self-efficacy has received support from a growing body of findings from diverse fields and applications 28 that pertain to business practice such as leadership 29 , self-development programs 30 , human capital 31 training 32 , education of entrepreneurship 33 , growing start-up companies 34 , internet involvement of SME:s 35 , gender and goal setting 36 , training proficiency, learning 37 , task persistence 38 , and goal directed behaviour 39 . Self-efficacy research is prevalent in other fields such as psychology and physiology with applications to clinical problems such as phobias 40 addiction 41 , social skills 42 , and assertiveness 43 to stress in a variety of contexts 44 and to health 45 .…”
Section: Validation Of the Definition Of Legal Efficacymentioning
confidence: 99%